Agricultural Value Chains in India Ensuring Competitiveness, Inclusiveness, Sustainability, Scalability, and Improved Finance - Gulati, Ashok; Ganguly, Kavery; Wardhan, Harsh (India Studies in Business and Economics,, 2022)
This open access book provides a clear holistic conceptual framework of CISS-F (competitiveness, inclusiveness, sustainability, scalability and access to finance) to analyse the efficiency of value chains of high value agricultural commodities in India. It is based on the understanding that agriculture is an integrated system that connects farming with logistics, processing and marketing. Farmer's welfare being central to any agricultural policy makes it very pertinent to study how a value chain works and can be strengthened further to realize this policy goal. This book adds value to the existing research by studying the value chains end-to-end across a wide spectrum of agricultural commodities with the holistic lens of CISS-F. It is not enough that a value chain is competitive but not inclusive or it is competitive and inclusive but not sustainable. The issue of scalability is very critical to achieve macro gains in terms of greater farmer outreach and sectoral growth. The research undertaken here brings out some very useful insights for policymaking in terms of what needs to be done better to steer the agricultural value chains towards being more competitive, inclusive, sustainable and scalable. The value chain specific research findings help draw very nuanced policy recommendations as well as present a big picture of the future direction of policy making in agriculture. .